Protest! : A History of Social and Political Protest Graphics - McQuiston, Liz (Book collections on Project MUSE., 2019)
An authoritative, richly illustrated history of six centuries of global protest art. Throughout history, artists and citizens have turned to protest art as a means of demonstrating social and political discontent. From the earliest broadsheets in the 1500s to engravings, photolithographs, prints, posters, murals, graffiti, and political cartoons, these endlessly inventive graphic forms have symbolized and spurred on power struggles, rebellions, spirited causes, and calls to arms. Spanning continents and centuries, Protest! presents a major new chronological look at protest graphics. Beginning in the Reformation, when printed visual matter was first produced in multiples, Liz McQuiston follows the iconic images that have accompanied movements and events around the world. She examines fine art and propaganda, including William Hogarth's Gin Lane, Thomas Nast's political caricatures, French and British comics, postcards from the women's suffrage movement, clothing of the 1960s counterculture, the anti-apartheid illustrated book How to Commit Suicide in South Africa, the "Silence=Death" emblem from the AIDS crisis, murals created during the Arab Spring, electronic graphics from Hong Kong's Umbrella Revolution, and the front cover of the magazine Charlie Hebdo. Providing a visual exploration both joyful and brutal, McQuiston discusses how graphics have been used to protest wars, call for the end to racial discrimination, demand freedom from tyranny, and satirize authority figures and regimes. From the French, Mexican, and Sandinista revolutions to the American civil rights movement, nuclear disarmament, and the Women's March of 2017, Protest! documents the integral role of the visual arts in passionate efforts for change.